A Comparative Analysis of Transcription Networks Active in Juvenile and Mature Wood in Populus - Luo, Laifu; Zhu, Yingying; Gui, Jinshan; Yin, Tongmin; Luo, Wenchun; Liu, Jianquan; Li, Laigeng (Frontiers in Plant Science, 2021)
Juvenile wood (JW) and mature wood (MW) have distinct physical and chemical characters, resulting from wood formation at different development phases over tree life-span. However, the regulatory mechanisms that distinguish or modulate the characteristics of JW and MW in relation to each other have not been mapped. In this study, by employing the Populus trees with an identical genetic background. we carried out RNA sequencing (RNA-seq) and whole genome bisulfite sequencing (WGBS) in JW and MW forming tissue and analyzed the transcriptional programs in association with the wood formation in different phrases. JW and MW of Populus displayed different wood properties, including higher content of cellulose and hemicelluloses, less lignin, longer and larger fiber cells and vessel elements in MW as compared to JW. Significant differences in transcriptional programs and patterns of DNA methylation were detected between JW and MW. The differences were concentrated in gene networks involved in regulating hormonal signaling pathways responsible for auxin distribution and brassinosteroids biosynthesis as well as genes active in regulating cell expansion and secondary cell wall biosynthesis. An observed correlation between gene expression profiling and DNA methylation indicated that DNA methylation affected expression of the genes related to auxin distribution and brassinosteroids signal transduction, cell expansion in JW and MW formation. The results suggest that auxin distribution, brassinosteroids biosynthesis and signaling be the critical molecular modules in formation of JW and MW. DNA methylation plays a role in formatting the molecular modules which contribute to the transcriptional programs of wood formation in different development phases. The study sheds light into better understanding of the molecular networks underlying regulation of wood properties which would be informative for genetic manipulation for improvement of wood formation.